. METHYLPREDNISOLONE EFFECTS ON SERUM BIOCHEMICAL FACTORS (CRP, PCT, IL-6, TNF-a) IN VIRAL PNEUMONIA: EFEKTI METILPREDNIZOLONA NA SERUMSKE BIOHEMIJSKE FAKTORE (CRP, PCT, IL-6, TNF-a) KOD VIRUSNE PNEUMONIJE - Zeng, Hongping; Zhu, Qi; Bai, Shaoyu; Liu, Jie; Ren, Dengjie; Chen, Xin (Journal of Medical Biochemistry, 2025)
Introduction: it was to demonstrate effects of methylprednisolone (MPS) and azithromycin treatment on serum biochemical factors and their impact on Serum Biochemical Factors (CRP, PCT, IL-6, TNF-α ) prognosis in patients with viral pneumonia (VP). Methods: 120 patients with VP admitted to our hospital were rolled into control (Ctrl), low-dose (80 mg MPS, L-MPS), medium-dose (500 mg MPS, M-MPS), and high-dose (1000 mg MPS, H-MPS) groups. The therapeutic efficacy of each group was evaluated. C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6) were detected. Pulmonary function parameters were assessed using a pulmonary function testing device. Adverse reactions (ARs) such as fever, nausea, vomiting, and gastrointestinal bleeding post-treatment were recorded. Results: total effective rate (TER) post-treatment in Ctrl group was 60.00%, which was inferior to that in L-MPS group (76.67%), M-MPS group (90.00%), and H-MPS group (93.33%) (P
Keywords: methylprednisolone; azithromycin; viral pneumonia; dosage; biochemical factors, CRP, PCT, IL-6, TNF-α